Alcohol cessation and breast cancer risk stratified by hormone receptor status - Mary Beth Terry; Dallas R. English; Jo L. Freudenheim; Béatrice Lauby-Secretan; Susan M. Gapstur (Breast Cancer Research)
Abstract Because alcohol consumption is an established cause of female breast cancer, understanding whether cessation affects risk is of public health importance. In a recent meta-analysis, compared with continuing consumption, the relative risk (RR) for cessation was 0.95 (95% confidence interval [CI] 0.88–1.01). Because intake of alcohol is more consistently associated with estrogen receptor positive (ER+) than negative (ER-) subtypes, we conducted a meta-analysis of alcohol cessation for ER-specific breast cancer risk using data from three cohort studies and one population-based case-control study (ER + n = 3,793; ER- n = 627) with information reported on cessation and ER status. Compared with continuing consumption, cessation was associated with lower risk of ER+ (RR = 0.88, 95%CI, 0.79–0.98) but not ER- (RR = 1.23, 95%CI, 0.98–1.55) breast cancer. These results suggest that, compared with continuing consumption, alcohol cessation may reduce ER + but not ER- breast cancer risk. However, research that considers duration of cessation is warranted.